Analytical Dimensions for Identifying Social Innovations: Evidence from Collective Enterprises - Ângela Maria Maurer; Tânia Nunes da Silva (BBR: Brazilian Business Review)
Social innovations are seen as alternatives to address social and environmental problems facing humanity. However, the term covers a broad range of definitions which can include a variety of initiatives. Based on analytical dimensions of social innovations, this study sought to assess to what extent the emergence of collective enterprises in the Brazilian handicraft sector is consistent with the dimensions postulated in the literature. Drawing on a multiple case study, the results showed that the analytical dimensions of social innovation identified the main elements involved in developing solutions with a significant number of actors, which indicates they are appropriate for understanding the formation of collective enterprises in the handicraft sector. This study has enabled, therefore, an understanding of how social solutions are built collectively and can be used to generate other social innovations or improvements to existing ones.